The genus Lecithocera (Lepidoptera: Lecithoceridae) from China, with descriptions of twenty-one new species - Shuai Yu; Shuxia Wang (European Journal of Taxonomy, 2024)
Twenty-one species of the genus Lecithocera Herrich-Schäffer, 1853 from China are described as new: L. angustifolia sp. nov., L. asticta sp. nov., L. balteiformis sp. nov., L. bicornuta sp. nov., L. bigeminata sp. nov., L. duplicispinea sp. nov., L. flavalba sp. nov., L. flavistriata sp. nov., L. furvibasis sp. nov., L. laticuculla sp. nov., L. ligulacea sp. nov., L. margirecta sp. nov., L. medogensis sp. nov., L. nullisigna sp. nov., L. parviflava sp. nov., L. parvispinea sp. nov., L. serratiloba sp. nov., L. sichuanensis sp. nov., L. tenuextrema sp. nov., L. tumicuculla sp. nov. and L. yunnanensis sp. nov. Seven species are newly recorded for China: L. alpestra Park, 2005, L. alpina Park, 2016, L. chersitis Meyrick, 1918, L. haviensis Park, 2016, L. neosticta Meyrick, 1918, L. orbiculata Park, 2010 and L. rubigona Park, 2006. The females of four species are described for the first time: L. alpina, L. haviensis, L. neosticta and L. orbiculata. Six new combinations are proposed: Lecithocera platomona (Wu, 1997) comb. nov. and L. stimulata (Wu, 1994) comb. nov. transferred from the genus Quassitagma; L. frisilina (Gozmány, 1978) comb. nov. transferred from the genus Recontracta; L. baliocata (Wu, 1994) comb. nov., L. sarmenta (Wu, 1994) comb. nov. and L. stictata (Wu, 1994) comb. nov. transferred from the genus Galoxestis. Images of adults and genitalia for all treated species are given, along with a checklist of all Chinese species of Lecithocera.